Correlation of surface and interfacial temperature during differential ultrasonic spot welding - Kaytie M. Barkley; Jaden S. Arner; Timothy A. Pike; Prasoon Diwakar; Cassandra M. Birrenkott (Journal of Advanced Joining Processes, 2023)
Ultrasonic spot welding (USW) has become an attractive joining method for thermoplastic polymers (TP) and thermoplastic matrix composites (TPMC). In the USW process, the material to be joined is subjected to mechanical vibrations of high frequency, causing intermolecular and surface friction which heat and melt the material at the joint interface. The interface resolidifies, resulting in a joint between two materials. In USW, it is necessary to focus the mechanical vibrations at the required weld location. A common method to accomplish this is to incorporate an energy director (ED) at the interface between materials to melt preferentially. However, incorporating EDs complicates the manufacturing process, particularly for large constant thickness polymer sheets. In this work, differential ultrasonic spot welding (DUS) is used which employs a flat horn and anvil of different diameters to initiate frictional heating between laminates at the desired joint location. This work investigates the effectiveness of DUS compared to a more traditional USW setup. Additionally, by measuring temperature at both the surface and the interface during DUS using infrared imaging and a thermocouple (TC), respectively, the driving factors behind the thermal profile of the welding process are examined. The goal of coupling the thermal profile to physical attributes of the DUS process is to eventually determine if variability present in the thermal profile may be tied to well-known joint area and strength variabilities.